PENERAPAN STRATEGI DIRECTED READING THINKING ACTIVITY UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DAN BERPIKIR KRITIS SISWA KELAS V UPTD SD NEGERI 3 JANGKA - Devitri Yusina; Alfi Syahrin; Muhammad Darwis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve reading comprehension skills while simultaneously sharpening the critical thinking abilities of fifth-grade students at UPTD SD Negeri 3 Jangka through the implementation of the Directed Reading Thinking Activity (DRTA) strategy. The main problem underlying this research is the low level of basic literacy and the passive involvement of students resulting from monotonous instructional methods. The approach applied in this study is qualitative-descriptive, using a Classroom Action Research (CAR) design conducted over two cycles, with each cycle encompassing planning, acting, observing, and reflecting phases. The results of the data analysis show a highly significant increase in learning outcomes from the first cycle to the second cycle. Students' classical mastery in Cycle I, which initially reached only 42.85%, experienced a drastic surge to 85.71% at the end of Cycle II, exceeding the predetermined success indicators. This increase in cognitive performance aligns with the optimization of the teacher's instructional execution, which increased from 78.8% to 95.5%, as well as the intensity of active student participation in the classroom, which soared from 68.8% to 94.45%. Based on the evaluation questionnaire, students gave a highly positive response to the DRTA tactic, with 55.71% expressing enthusiasm and 43.33% stating agreement. It can be concluded that the DRTA strategy is empirically proven to be highly effective in boosting the quality of reading comprehension, stimulating critical reasoning, and constructing an interactive, student-centered learning atmosphere in elementary schools.